2021
DOI: 10.1016/j.prp.2021.153381
|View full text |Cite
|
Sign up to set email alerts
|

RNase in the saliva can affect the detection of severe acute respiratory syndrome coronavirus 2 by real-time one-step polymerase chain reaction using saliva samples

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a single-stranded RNA virus that causes coronavirus disease 2019, which spread worldwide immediately after the first patient infected with this virus was discovered in Wuhan, China, in December 2019. Currently, polymerase chain reaction (PCR) specimens for the detection of SARS-CoV-2 include saliva, nasopharyngeal swabs, and lower respiratory tract-derived materials such as sputum. Initially, nasopharyngeal swab specimens were applied mainly to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Indeed, some studies suggested that pretreatment of samples with PK increased the sensitivity of direct rRT‐PCR for SARS‐CoV‐2 detection, 28,29 particularly in low positive samples with high C t values 13 . It has been suggested that PK could degrade or inactivate RNAses, allowing to purify a better quality of RNA 30 . Another study showed that sputum specimens pretreated with PK for homogenization before nucleic acid extraction for RT‐PCR had a higher detection rate than those pretreated with saline only.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies suggested that pretreatment of samples with PK increased the sensitivity of direct rRT‐PCR for SARS‐CoV‐2 detection, 28,29 particularly in low positive samples with high C t values 13 . It has been suggested that PK could degrade or inactivate RNAses, allowing to purify a better quality of RNA 30 . Another study showed that sputum specimens pretreated with PK for homogenization before nucleic acid extraction for RT‐PCR had a higher detection rate than those pretreated with saline only.…”
Section: Discussionmentioning
confidence: 99%
“…Saliva is a source of RNases that may degrade the SARS-CoV-2 RNA genome, compromising its detection by RT-qPCR [18]. To overcome this situation, we added the thermostable RNase inhibitor Poly-Vinyl Sulfonic Acid (PVSA) to the PKT buffer (hereafter PKTP), a low cost-reagent that can enhance RNA preservation at low concentrations [19].…”
Section: Resultsmentioning
confidence: 99%
“…This buffer is compatible with a heat-inactivation step that has been previously demonstrated to eliminate SARS-CoV-2 in saliva [13, 22], minimizing the biohazard risks of handling the samples. However, RNA degradation is a concern when heating or storing samples, as saliva contains thermo-stable RNases that may compromise the diagnosis [18]. Our own data showed that storage of saliva resulted in low molecular weight RNA molecules indicative of degradation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, serial dilution rate with the saliva sample was highly correlated to Ct value with equivalent to Tris buffer. As several studies have reported, salivary RNA is prone to degradation by RNases and other nucleases present in saliva [27, 28]. Hence, it was concluded that this method made it possible to detect virus in saliva without treating in advance (extraction, purification, concentration, etc.…”
Section: Discussionmentioning
confidence: 99%